RELEVANSI NILAI DAN KEMUNGKINAN DETERIORASI: KAJIAN LITERATUR SISTEMATIK - Randy Kuswanto (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2020)
The paper presents the review of the value relevance literatures used Ohlson model (1995). The popularity of value relevance topic nowadays is principally driven by the adoption IFRS which changed how companies measure its income and assets. Although this topic is still in debate whether it useful or not, this paper tried to conclude a summary from many prior value relevance researches. First, I seek to review some of the significant literature on value relevance during 2009-2019. The emphasis is on results and empirical contributions relating incremental value relevance. The second part of this paper is discussion about eight different studies from more than 10 countries about evidence of value relevance phenomenon in their setting. This paper finds that the concept of value relevance really exists in many countries but it is deteriorating / declining over the period. Further research could test other information to prevent this deterioration of value relevance such as future prospect attributes rather than historical information only